Emphasizing excellence and diversity cues on university websites: Additive or interactive effects on prospective students' psychological reactions? - Ihme, Toni Alexander; Stürmer, Stefan (Journal of applied social psychology, 2018)
A series of three web‐based scenario experiments investigated how emphasizing excellence and/or diversity on university websites affects students' psychological reactions toward the advertising institution. Our findings form a robust pattern suggesting that emphasizing excellence and emphasizing diversity have additive (rather than interactive or mutually interfering) effects. Two studies (N = 346 and N = 128) showed that the effects of emphasizing excellence and diversity arise from different psychological processes related to important aspects of student applicants' expectations about how well they “fit in” and how well the institution will meet their needs. Study 3 (N = 363), using a within‐subject design, further corroborated that participants preferred universities whose websites emphasized both excellence as well as diversity. Practical implications and directions for future research are discussed.